Effects of Electric Field and External Magnetic Field on the Electronic and Thermoelectric Properties of the h-BAs Monolayer and Bilayer: Tight-Binding Approach. (1st December 2022) - Abdi, Mona; Norian, Erfan; Astinchap, Bandar; Ghobadi, Nader; Frozan, Fazlahmad
Abstract : Newly, two-dimensional (2D) materials atoms of groups IV and III-V have obtained extensive attention due to their novel properties. In this work, we apply the tight-binding model and Green's function approach to the hexagonal boron arsenide (h-BAs) monolayer and bilayer to investigate their electronic and thermoelectric properties. We find that the h-BAs monolayer behaves as a p-type semiconductor and it can be changed to the n-type by applying the external magnetic field. Also, the h-BAs bilayer with (A-A) stacked has a semi-metallic property but (A-B) stacked is a semiconductor. The results show that the band gap can be controlled by applying an electric field and an external magnetic field. We obtain that the thermal and electrical conductivity of the h-BAs monolayer and bilayer increase in the presence of an electric field and an external magnetic field. More, controlling the Seebeck coefficient of the material is a unique phenomenon that provides advanced applications for these materials in thermoelectric coolers and waste heat harvesting. Here, we have been able to regulate the Seebeck coefficient of the h-BAs monolayer and bilayer by using the electric and external magnetic fields.